2006
DOI: 10.1590/s0103-65642006000400013
|View full text |Cite
|
Sign up to set email alerts
|

Alterações cognitivas, comunicativas e emocionais após lesão hemisférica direita: em busca de uma caracterização da Síndrome do Hemisfério Direito

Abstract: Universidade Federal do Rio Grande do Sul -UFRGS O conjunto de sinais e sintomas observados após um acometimento neurológico no hemisfério direito pode ser denominado de Síndrome do Hemisfério Direito -SHD. Esse ensaio teórico tem por objetivo apresentar uma caracterização desse quadro neuropsicológico. A SHD é, então, caracterizada por défi cits nas funções cognitivas atenção 242R. P. Fonseca, G. D. Ferreira, F. V. Liedtke, J. L. Müller, T. F. Sarmento e M. A. M. P. Parente O interesse pela dicotomia hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
0
12
0
8
Order By: Relevance
“…Studies conducted to date investigated communication in neurological populations and healthy individuals. In samples of healthy individuals, the effects of age and education on communicative skills have been investigated (Fonseca, Ferreira, Liedtke, Muller, Sarmento, & Parente, 2006). More specifically, the effect of education was more frequent and robust than the effect of age, with some interactions suggesting a minor role for education with increasing age.…”
Section: Studies On Language In the Right Hemispherementioning
confidence: 99%
“…Studies conducted to date investigated communication in neurological populations and healthy individuals. In samples of healthy individuals, the effects of age and education on communicative skills have been investigated (Fonseca, Ferreira, Liedtke, Muller, Sarmento, & Parente, 2006). More specifically, the effect of education was more frequent and robust than the effect of age, with some interactions suggesting a minor role for education with increasing age.…”
Section: Studies On Language In the Right Hemispherementioning
confidence: 99%
“…The cognitive, communicative and emotional consequences of right hemisphere lesions are collected referred to as Right Hemisphere (RH) Syndrome (see Fonseca et al 2006). Studies of RH syndrome have also uncovered communicative deficits and impairments in EF.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity may be related to inhibitory control and perseveration, which implies that the RH is involved in inhibition of impulsive responses. Fonseca et al (2006) reported that patients with damage in RH tend to respond quickly and impulsively on behavioural tasks, resulting in poor performance. Taken together these findings suggest that further investigation of EF deficits and impulsivity following RH damage is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…These damages can be grouped into motor, cognitive, communicative and behavioral/emotional deficits, besides swallowing disorders and urinary incontinence (2) . The right hemisphere (RH) is involved in several cognitive functions such as memory (3) , temporal and spatial orientation (4) , attention (5) and praxis (6) . RH has important role in language, specifically in functional language aspects (1) .…”
Section: Introductionmentioning
confidence: 99%